Establishment of a genotyping criteria for Bandavirus dabieense and confirmation of new genotypes - Bingyan Liu; Tengfei He; Changtai Wang; Guomei Xia; Shijun Zhou; Shanshan Sun; Xinlei Chen; Xiaodan Hong; Jie Zhu; Zhenhua Zhang (Scientific Reports)
Abstract Bandavirus dabieense (DBV) causes severe fever with thrombocytopenia syndrome, which has a mortality rate of 6.18% of 27%. DBV has been classified into five to six genotypes using phylogenetic analyses. However, the absence of clear standards poses challenges in identifying new genotypes. We performed evolutionary and homology analyses using the sequences from GenBank and analysed nucleotide differences between the different genotypes. Nucleotide differences within the same genotype were mostly below 3%, whereas those between different genotypes ranged from 3 to 7%. Consequently, we established and validated a specific genotyping criterion for DBV using phylogenetic tree analysis with a 3% cut-off value and identified 8, 11, and 11 genotypes in the S, M, and L segments, respectively. Furthermore, we compared our method with the previous genotyping methods to elucidate the convenience and advantages of using a 3% cut-off value. Importantly, we also identified new genotypes and fragment reassortments in DBV using our new genotyping criterion. Additionally, we established two simplified genotyping methods for the rapid typing of DBV in clinical settings and demonstrated the existence of geographical and clinical variations among the different genotypes. Our findings provide a more reliable foundation for clinical typing of DBV.